Marketing Ecosystem: Competitive Benefit beyond View - KHARE, DR. ASHISH (The journal of contemporary issues in business and government, 2021)
The word business model has been used frequently in boardrooms by organizational administrators, advisors, industry analysts and even broadcasting services targeted at the population at large. One function of business models is to include a collection of general levels of knowledge about how an organization organizes itself in a productive way to generate and deliver value. The paper discusses about the perspective on the brand environments consisting of few factors for marketing ecosystem. The major trends in marketing has also been discussed comprising market place trends, technological trends, socio-economic trends, geopolitical trends and environment trends. The discussion suggests about the multivalent essence of business as models. They could be found as illustrations of role models which can be replicated or used as a concise business entity description: simplistic short-hand descriptions that are similar to standard scales. We should think such that these are not only captured in the universe (within a taxonomy) as features of the observed types, but rather as abstract ideal forms in the way outlined by Webber. In the empirical context, market models often act as models. They are templates (as in biology) that reflect groups of things. They may be studied. Or they can appear as schemas in scholarly slides and as representations misleading like economic models in which they appear as generalized intermediate forms of explanations like science models in many fields that are neither universal nor complete empirical definition.